Synthesis, characterisation and application of biopolymer films incorporated with natural additives for food preservation - Al Luqman Abdul Halim (Tanjong Malim, 2018)
Synthesis, characterisation and application of biopolymer films incorporated with natural additives for food preservation by Al Luqman Abdul Halim